Lactobacillus plantarum in Dual-Species Biofilms With Listeria monocytogenes Enhanced the Anti-Listeria Activity of a Commercial Disinfectant Based on Hydrogen Peroxide and Peracetic Acid - Bonneville, Lourenço; Maia, Vera; Barroso, Inês; Martínez-Suárez, Joaquín V.; Brito, Luisa (Frontiers in Microbiology, 2021)
The aim of this work was to investigate the effect of dual-species biofilms of Listeria monocytogenes with Lactobacillus plantarum on the anti-Listeria activity of a hydrogen peroxide/peracetic acid based commercial disinfectant (P3, Oxonia) when using conditions approaching the food industry environment. Nine strains of L. monocytogenes, including eight persistent strains collected from the meat industry and one laboratory control strain, were used in mono and in dual-species biofilms with a strain of L. plantarum. Biofilms were produced on stainless steel coupons (SSC), at 11°C (low temperature) or at 25°C (control temperature), in TSB-YE (control rich medium) or in 1/10 diluted TSB-YE (mimicking the situation of biofilm formation after a deficient industrial cleaning procedure). The biofilm forming ability of the strains was evaluated by enumeration of viable cells, and the antibiofilm activity of P3 was assessed by log reduction of viable cells on SSC. In both nutrient conditions and at low temperature, there was no significant difference (p > 0.05) between L. monocytogenes biofilm forming ability in mono- and in dual-species biofilms. In dual-species biofilms, L. monocytogenes was the dominant species. However it was generally more susceptible to the lower concentration of P3 0.5% (v/v) than in pure culture biofilms. The presence of L. plantarum, although without significant interference in the number of viable cells of L. monocytogenes, enhanced the efficacy of the anti-Listeria activity of P3, since dual-species biofilms were easier to control. The results presented here reinforce the importance of the investigation into co-culture biofilms produced in food industry conditions, namely at low temperatures, when susceptibility to sanitizers is being assessed.